Diesel−biodegradation and biosurfactant−production by Janthinobacterium lividum AQ5-29 and Pseudomonas fildesensis AQ5-41 isolated from Antarctic soil - Yap, How Swen; Khalid, Farah Eryssa; Wong, Rasidnie Razin; Convey, Peter; Sabri, Suriana; Khalil, Khalilah Abdul; Zulkharnain, Azham; Merican, Faradina; Shaari, Hasrizal; Ahmad, Siti Aqlima (Elsevier, 2024)
Given the substantial diesel demand in Antarctic operations, the means of addressing ecological restoration following its inappropriate release are attracting attention from researchers. The Madrid Protocol mandates the use of indigenous microbes in bioremediation. Recent studies have proposed many native isolates with biodegradation temperatures exceeding 20 °C, which are impractical for Antarctic contexts. Therefore, harnessing psychrophilic, native degraders with biosurfactant−producing traits presents an advantage for implementation in the harsh Antarctic environment. In this study, effective consortia/isolates demonstrated robust growth and biodegradation rates at 10 °C with diesel as the sole carbon source. Two primary bacterial members, Janthinobacterium lividum and Pseudomonas fildesensis, were identified from the most effective consortium SI 20 using 16S rRNA and multilocus−sequence−analysis (MLSA) clustering. The degraders were characterised as being psychrophilic, Gram-negative, rod−shaped, and catalase− and oxidase−positive. Despite the observed antagonistic effects during co-cultivation, strains J. lividum AQ5-29 and P. fildesensis AQ5-41 demonstrated effective diesel removal (2.91 & 4.20 mg mL−1) with biodegradation of C10 to C30 hydrocarbons (40−100) at 10 °C in less than 8 days. Both strains also were identified as biosurfactant producers with varying emulsification activities (32−92) and cell surface hydrophobicity (52−58). These findings highlight the potential of both strains for restoring diesel-related substrates, particularly in Antarctica.